A comparison of outcomes of four ports versus three ports laparoscopic cholecystectomy - Koirala, K.; Simkhada, G.; Adhikari, N.; Mukhia, R.; Shakya, S. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Conventional laparoscopic cholecystectomy is performed using four ports. With increasing surgeon experience, there is a trend towards performing it using three ports. The aim of this study was to compare the three-port laparoscopic cholecystectomy with the conventional four-port technique in terms of safety, benefits and feasibility in a teaching hospital and private hospital setups.Materials & Methods: A retrospective review of medical records was performed on patients who underwent laparoscopic cholecystectomy at KIST Medical College and Teaching Hospital and Om Hospital & Research Center P. Ltd by a single laparoscopic surgeon. The review included demographics, operating time, analgesics requirement, post- operative hospital stay and intra-operative and post-operative complications. The data were tabulated in MS-Excel and statistically analyzed using SPSS statistics software, version 21.Results: There were 150 patients included in this study with 75 patients in each three and four-port groups. The demographics were comparable in both groups. 7.3% were diagnosed with acute calculous cholecystitis, 76.7% with chronic calculous cholecystitis and 3.3 % were gall bladder polyps. Four-port technique was generally required for the acute calculous cholecystitis which was statistically significant. The three-port group had a shorter mean operative time than the four-port group. There was no statistically significant difference in the doses of analgesics requirement and mean post-operative hospital stay in both groups. There were no major intra and post-operative complications in both groups. Four-port technique was commonly done in teaching hospital and the three-port in private hospital.Conclusions: There is significant number of laparoscopic cases being performed using three ports and we concluded that the three-port laparoscopic cholecystectomy is safe and feasible in experienced hand although there is no significant benefit. The study also showed an increasing use of four-port technique in the teaching institution which is better to clearly visualize the anatomy of the Calot’s triangle. So we recommend using the four-port technique for teaching the beginners and as the experience is gained, we can gradually shift to three-port technique and at the same time we shouldn’t hesitate to convert to four-port in difficult cases.JMMIHS.2018;4(1):66-71